Honours as a lab for education development and international cooperation - Carien Touwen; Elvira van Noort (Journal of the European Honors Council)
Back in 2015 everyone in the field of journalism was grappling with a media landscape that presented significant and fast-paced challenges, for better and worse. Digitalisation had created free and open access to online media, new audiences, storytelling possibilities, better options to gain and trace information, but also an unregulated internet with little privacy protection and a dark (hidden) online reality; all steered by technological developments (Digital News Report, Reuters 2015). Journalism educators struggled to adapt their curricula in time: change was the new normal (Lynch, 2015). It was however evident from, for example, the unprecedented growth of fake news that teaching advanced verification and fact-checking would be essential for the professional future of young journalists.